OVERBURDENED TERMS. - A. C. L. (The Accounting Review, 1931)
Anyone who indulges in a mental résumé of major topics of accounting discussion for recent years would probably emerge with one or the other of two convictions, either one is rapidly drifting away from moorings of older conceptions of basic elements of accountancy, or that one is growing with considerable rapidity in new directions. The word capital for example, has long been used as a term to indicate the investment brought into a business by proprietory interests. It was distinctly associated with contribution. Statutory regulations concerning limited liability corporations further emphasized this concept by requiring that the proposed sum of capital be definitely stated from the very inception of the organization, that it be fully paid in and that it be maintained intact against the encroachment of dividends. Capital stock was considered by legislatures and courts as representing owners' contribution, the amount dedicated to purposes of the business by those controlling the concern's affairs and enjoying residual profits, if any. Is accounting thought drifting away from this and other basic conceptions, or is it is merely growing out of garments in which it has for so long been clothed? No-par stock has brought occasional presentations of financial structures in which original contribution was divided between capital stock and initial surplus.